SAT0290 Prospective Observational Study of 5-Year Follow-Up of Distal Radius Fractures in a Trauma Center. (9th June 2015) - Lisbona, M.; Aguilera, C.; Leon, P.; Anaya, M.; Rubio, E.; Povedano, J.; Muñoz, M.
Abstract : Background: Distal radius fracture is considered the first fragility fracture. A linear increase of these fractures in women over age 55 is observed. Objectives: To describe the baseline characteristics of patients over 55 years with a diagnosis of Distal radius fracture initially treated in the Emergency area and required hospitalization in 2009 in the Traumatology and Rehabilitation Hospital Virgen del Rocío de Sevilla and monitoring after over 5 years. Methods: Prospective observational study of 5-year follow-up of a cohort of patients, women older than 55 years who required surgery in 2009 of Distal radius fracture occurred by accidental fall, excluding traffic accidents and precipitation and if the risk of osteoporosis was evaluated during follow-up over the next 5 years. Baseline characteristics were studied: age, smoking, taking steroids, personal history of Rheumatoid Arthritis, if they had previous bone densitometry and the presence of previous fragility fractures. During follow assessed whether patients were referred to Rheumatology to assess risk of Osteoporosis, if bone densitometry later, if presented after osteoporotic fractures (vertebral, non hip peripheral fractures and hip fractures) and if received specific treatment for the Osteoporosis Results: 52 women were included in the study with a mean age of 69.69±8.748 years. 55-88 years range. Between baseline characteristics studied were found 5.8% (3 patients.) Were smokers, 13.2% (7 patients.) Were steroid takers regularly, 3.8% (2 patients.) With Rheumatoid Arthritis, 9.6% (5 patients.) had a history of previous fragility fractures. During the follow up period of 5 years 14 patients (26.9%) had osteoporotic fractures, including vertebral fractures 6 patients found. (11.5%), peripheral non hip fractures 5 patients. (9.6%) and hip fractures 4 patients. (7.7%). 12 patients were derived. (23.1%) a Rheumatology specialist for risk assessment of Osteoporosis, 9 patients. (17.3%) underwent bone densitometry and 10 patients (19.2%) received specific treatment for Osteoporosis. Conclusions: Distal radius fracture is the result of a fall on an outstretched arm. It is considered the first fragility fracture. Presents an increased incidence after 55 years. In our study, it is noteworthy that 26.9% of patients who suffered a Distal radius fractured submitted an osteoporotic fracture during the follow up period of 5 years, including 7.7% were hip fractures in consequent increase in morbidity and mortality. However, only 23% of patients were referred to Rheumatology for risk assessment of Osteoporosis. Therefore, we must continue to emphasize proper evaluation of Osteoporosis risk of these fractures in the Emergency area. Disclosure of Interest: None declared